(3JYQja Cgd GdJbOjS HeQGJH GdehUhajf HGdJOdjSs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPg eYQaI eQGJH GdehUhajf HGdJOdjS ai CSGfjO GdMOjK GdfHhi s
(3BNQgG (B:s
(3aSCdJg (B: (3CSeYJ gPG cdg Yf LGHQ? bGd dG, ajg eGSeYJg hajg eG (B[(3de(B](3CSeYg bdJ(B: (3aCYde di Ydi eGSeYJg efg(B: (3aCYde di Ydi gPG GdPi YfOj, hGddg CYde s
(3Vef eLehY s
(3GfXQ Qbe (B180 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
Keywords: (3GdJGQjNs